Kemampuan dan kemauan membayar premi asuransi kesehatan di Kabupaten Gunung Kidul = Willingness and ability to pay health insurance in Gunung Kidul - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Background: The economic analysis of many health policies especially in the development of health insurance or managed health care requires assessment on the ability to pay (ATP) and willingness to Pay (WTP) of the community. This study was conducted to assess the ATP and WTP as well as the intention of the Gunung Kidul community to participate in the development of the local managed care system. Methods: A cross-sectional study design was used in this study. Study population consisted of 600 households chosen by using a stratified random sampling. Data on the characteristics of the subjects, health expenditures, ability and willingness to pay and intention to participate in the local managed health care was collected by using tested structured questionnaire. Results: The majority of the respondents has the willingness to pay for out patient and inpatient care per visit and per admission was Rp 10.000 and less than Rp 300.000 respectively. However, the ability of the community is more than Rp. 60.000 per household per month. More than 70% of the respondents were interested to participate in the local managed health care and the willingness to pay for premium per month per person of the plan was Rp. 2000. Conclusions: Majority of respondents have intention to participate in the local managed health care and have satisfactory ability to pay for the premium, however, the willingness to pay of the premium is still below expectation.